The DYT6 Dystonia Protein THAP1 Regulates Myelination Within The Oligodendrocyte Lineage - Yellajoshyula, Dhananjay (Dev Cell, 2017)
The childhood-onset motor disorder DYT6 dystonia is caused by loss-of-function mutations in the transcription factor THAP1, but the neurodevelopmental processes in which THAP1 participates are unknown. We find that THAP1 is essential for the timing of myelination initiation during CNS maturation. Conditional deletion of THAP1 in the CNS retards maturation of the oligodendrocyte (OL) lineage, delaying myelination and causing persistent motor deficits. The CNS myelination defect results from a cell autonomous requirement for THAP1 in the OL lineage, and is recapitulated in developmental assays performed on OL progenitor cells purified from Thap1 null mice. Loss of THAP1 function disrupts a core set of OL maturation genes and reduces the DNA occupancy of YY1, a transcription factor required for OL maturation. These studies establish a role for THAP1 transcriptional regulation at the inception of myelination, and implicate abnormal timing of myelination in the pathogenesis of childhood-onset dystonia.